Penicillin resistant Streptococcus pneumoniae - Abd Hamid, Mohd Zaini; Ting, Tzer Hwu; Othman, Norlijah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2008)
Antibiotic resistance is uncommon in paediatric community acquired pneumonia (CAP) in Malaysia. However, with the increased use of antibiotics, there is a risk of penicillin-resistant Streptococcus pneumoniae (PRSP) pneumonia which results in antibiotic treatment failure. We report here a case of CAP complicated by empyema, caused by PRSP, which presented as acute respiratory distress in a 19-month-old boy.